51.2k views
0 votes
How to simplify (4•4-3•1-3•3)\[0-(-2)•(-2)

User Zsltg
by
4.9k points

2 Answers

3 votes

Use PEMDAS

P Parentheses first

E Exponents (ie Powers and Square Roots, etc.)

MD Multiplication and Division (left-to-right)

AS Addition and Subtraction (left-to-right)


(4\cdot4-3\cdot1-3\cdot3)/(0-(-2)\cdot(-2))=(16-3-9)/(-4)=(4)/(-4)=-1

User Jglasse
by
5.7k points
4 votes

(4•4-3•1-3•3)\[0-(-2)•(-2)]

complete the parenthesis first

(4•4-3•1-3•3)

complete the multiply and divided first from left to right

16 -3-9 =

then complete the subtraction

13-9 =4

now

[0-(-2)•(-2)]

complete the parenthesis first

do the multiplication

-2*-2

4

now subtract

0-4=-4

so we have

-4/4

Answer: -1


User TapanHP
by
5.3k points